Pengaruh Outdoor Recreation Motivation Terhadap Revisit Intention Melalui Perceived Risk - Millah, Ana Inayatul; Mulyadi, Hari; Ridwanudin, Oce (STIEPAR YAPARI Bandung, 2024)
Repeat visits made by tourists become one of the assessment factors regarding overall customer satisfaction, destination maturity, and perceived value of a tourist destination when tourists make a visit. Empirical research has recognized that many attractions and tourist destinations are very dependent on tourists who reivisit. Based on the above, conducting research on revisit intention will greatly help the company or destination to maintain its existence and provide an advantage in its competitiveness. The purpose of this study is to obtain an overview and influence of the outdoor recreation motivation dimension on revisit intention tought perceived risk in tourists Jamiaki Peak and Puspa Peak Camp Destination, Ciamis Regency. The research method used is a quantitative method. The study was conducted by setting a sample of 350 tourists through questionnaires as data collection. The study used SEM (Structural Equation Model) analysis techniques with AMOS 20.0 software and SPSS for windows version 25.0. Tests have shown that outdooor recreation motivation has a significant effect simultaneously on revisit intetion through perceived risk. The results of the Parameter Estimation Model of outdoor recreation motivation on revisit intention through perceived risk as a whole have been known that the R2 value of 0.443 means that the variable revisit intention which can be explained by outdoor recreation motivation intention and perceived risk is 44.3%, while 55.7% is influenced by other variables.